Identification of efficient prokaryotic cell-penetrating peptides with applications in bacterial biotechnology - Hyang-Mi Lee (Nature Portfolio, 2021)
Lee et al. construct a cell-penetrating peptides (CPP) library and identify CPPs that can penetrate bacterial cells with minimum or no impact on cell viability. For the identified top CPP candidates, their abilities to deliver macromolecules such as I-SceI and Cre recombinase proteins to bacteria are evaluated as proof-of-concept studies for potential applications.